Sustainable multilingualism 2019 : 5th international scientific conference of Institute of Foreign Languages, Vytautas Magnus University & 13th international scientific conference of Language Teachers' Association of Lithuania May 24-25, 2019 Kaunas, Lithuania : conference abstracts - Mačianskienė, Nemira (editor) (Vytautas Magnus University, 2019)
5th international scientific conference of Institute of Foreign Languages, Vytautas Magnus University & 13th international scientific conference of Language Teachers' Association of Lithuania May 24-25, 2019 Kaunas, Lithuania.